(untitled) (Revista de Estudos da Linguagem, 2019)
Abstract: The aim of this research was to evaluate the distribution of DPs in generic sentences, in Dutch Heritage Language Speakers (HLS) in Holambra, Brazil, especially regarding the acceptability of Bare Singular Count Nouns (BS). The Distribution of BS is more restricted in Dutch than in Brazilian Portuguese, nonetheless, we raised the hypothesis that, due to the influence of Brazilian Portuguese, these HLS would accept BS in contexts similar to those of Brazilians. We applied an acceptability judgement test to 60 adult HLS from Holambra (experimental group), 30 Brazilian monolinguals and 30 native Dutch speakers (control groups 1 and 2). We presented to each participant in the experimental group 10 Dutch stimulus sentences and 20 filler sentences in order to verify their acceptability on a five-item Likert scale. The results showed that sentences with BS eliciting a generic reading received high acceptability rates from the Experimental Group of Holambra (72% acceptability rate). These responses were more aligned with the Brazilian Control (78% acceptability rate) than with the Dutch Control (96% unacceptability rate). The statistical Regression Analysis of the BS showed that the Dutch Control had a significant divergent behavior (p.value = <2-16) when compared to the Experimental Group. The results seem thus to support our hypothesis that a slightly different grammar has risen in the Dutch HLS of Holambra, suffering attrition due to the influence of Brazilian Portuguese, since they accept Bare Singulars, showing no significant difference with the Brazilian Control Group. We will follow Oosterhof’s proposal (2008) on the distribution of empty determiners in Dutch and assume that the grammar of the Holambra speakers possesses a bundle of features allowing a 0[+R, +count, –pl] combination: That is, a singular count noun DP with an empty determiner, rendering a generic reading. Keywords: language acquisition; heritage languages; bare singular count nouns; Dutch; Brazilian Portuguese. Resumo: O objetivo desta pesquisa foi avaliar a distribuição de DPs em sentenças genéricas em falantes de neerlandês como língua de herança em Holambra, Brasil, especialmente em relação à aceitabilidade de nomes singulares nus (NNs). A distribuição de NNs é mais restrita em neerlandês do que no Português Brasileiro (PB), no entanto, levantamos a hipótese de que, devido à influência do PB os falantes de Holambra poderiam aceitar NNs em contextos semelhantes aos dos brasileiros. Aplicamos um teste de aceitabilidade em 60 HLS adultos de Holambra (grupo experimental), 30 monolíngues brasileiros e 30 falantes nativos de holandês (grupos de controle 1 e 2). Apresentamos a cada participante do grupo experimental 10 sentenças em neerlandês e 20 distratores, a fim de verificar sua aceitabilidade em uma escala Likert de cinco itens. Os resultados mostraram que sentenças genéricas com NNs receberam alta aceitação do Grupo Experimental de Holambra (72% de aceitabilidade). Essas respostas estão mais alinhadas com o Controle Brasileiro (78% de aceitabilidade) do que com o Controle Holandês (96% de inaceitabilidade). A análise de regressão estatística dos NNs mostrou que o Controle Holandês apresentou comportamento significativamente divergente (p. valor=<2-16) quando comparado com o Grupo Experimental. Os resultados parecem corroborar nossa hipótese de que uma gramática ligeiramente diferente surgiu nos falantes de holandês de Holambra, sofrendo atrito devido à influência do PB, uma vez que aceitam NNs, não mostrando diferença significativa com o Grupo de Controle Brasileiro. Seguiremos a proposta de Oosterhof (2008) sobre a distribuição de determinantes vazios em holandês, e propor que a gramática dos falantes de Holambra possui um conjunto de traços permitindo a combinação 0 [+ R, + count, -pl]: isto é, um nome nu singular contável com uma leitura genérica. Palavras-chave: aquisição de linguagem; línguas de herança; nomes singulares nus; neerlandês; português brasileiro.